Corrigendum to “Hydrothermal geochemical signatures in zircon as a pathfinder for IOCG mineralization: An example from the Carajás Mineral Province (Brazil)” [J. Geochem. Explor. 281,107934 (2026)] - Maurício L. Borba; Colombo C. Tassinari; Fernando M. Matos; John M. Hanchar; Fernando Tornos; Sergio Huhn; Kei Sato (Journal of Geochemical Exploration, 2026)

Toward Sustainable Rainbow Trout Lipid Nutrition: A Systematic Review of Lipid Optimization Strategies in Controlled Conditions - Rosendo L. Azcuy; Alejandro Villasante; Susana Perelman; Matías E. Casaretto; Patricio Dantagnan; Gabriel A. Morales; Stefanie Colombo (Reviews in Aquaculture, 2026)
Replacing fish oil (FO) in feeds remains a challenge for aquaculture sustainability. While experimental studies have evaluated the effects of alternative lipids on fillet long‐chain polyunsaturated fatty acids (LC‐PUFA) in rainbow trout, a quantitative synthesis of these effects is lacking. Here, 119 experimental diets from 29 controlled studies were synthesized through a statistical framework combining linear mixed‐effects models (LMM), generalized additive models (GAM), and leave‐one‐study‐out validation. Dietary docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA) consistently predicted fillet DHA and EPA concentrations, independent of growth rate and not significantly influenced by temperature or lipid level. While growth performance was unaffected by FO replacement, LC‐PUFA deposition was not equivalent across lipid origins: FO and vegetable‐based diets supported steeper diet‐to‐fillet transfer slopes compared to animal‐derived lipids. GAMs revealed non‐linear thresholds, with active deposition occurring only when dietary LC‐PUFA exceeded near 10 mg g −1 and the dietary n‐6:n‐3 ratio remained below approximately 4. Temperature, modelled linearly, showed no significant effect on fillet LC‐PUFA deposition within the analysed dataset. These results demonstrate that FO can be reduced without compromising growth, but not without reformulating LC‐PUFA supply and precursor balance. Successful FO replacement is therefore a formulation problem rather than an ingredient substitution issue. Emerging sources such as algal oils or engineered oilseeds represent a viable pathway toward sustainable feeds delivering nutritionally valuable fillets. The identified dietary thresholds provide practical guidance for feed formulation by defining minimum LC‐PUFA inclusion levels and n‐6:n‐3 ratios required to achieve target fillet EPA and DHA concentrations under controlled temperature conditions.

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Hydrothermal geochemical signatures in zircon as a pathfinder for IOCG mineralization: An example from the Carajás Mineral Province (Brazil) - Maurício L. Borba; Colombo C. Tassinari; Fernando M. Matos; John M. Hanchar; Fernando Tornos; Sergio Huhn; Kei Sato (Journal of Geochemical Exploration, 2026)

P18-36 “Cross-species” Liver Microtissues: Species-specific microphysiological test systems for comparative toxicological in vitro studies during nonclinical drug safety assessment - M.V. Colombo; F. Wenz; L. Fäs; A. Pawlowska; A. Wolf; B.G. Filippi (Toxicology Letters, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

P12-05 Species-specific liver microtissues: a set of micro-physiological systems to study translational hepatotoxicity in safety assessment - M.V. Colombo; F. Wenz; L. Fäs; A. Borgström; A. Wolf; B.G.H. Filippi (Toxicology Letters, 2024)

Unveiling Trichosporon austroamericanum sp. nov.: A Novel Emerging Opportunistic Basidiomycetous Yeast Species - Elaine C. Francisco; Marie Desnos-Ollivier; Chendo Dieleman; Teun Boekhout; Daniel Wagner de C. L. Santos; José O. Medina-Pestana; Arnaldo L. Colombo; Ferry Hagen (Mycopathologia, 2024)
During an epidemiological survey, a potential novel species within the basidiomycetous yeast genus Trichosporon was observed. The clinical strain was obtained from a urine sample taken from a Brazilian kidney transplant recipient. The strain was molecularly identified using the intergenic spacer (IGS1) ribosomal DNA locus and a subsequent phylogenetic analysis showed that multiple strains that were previously reported by other studies shared an identical IGS1-genotype most closely related to that of Trichosporon inkin . However, none of these studies provided an in-depth characterization of the involved strains to describe it as a new taxon. Here, we present the novel clinically relevant yeast for which we propose the name Trichosporon austroamericanum sp. nov. (holotype CBS H-24937). T. austroamericanum can be distinguished from other siblings in the genus Trichosporon using morphological, physiological, and phylogenetic characters.

When another one bites the dust: Environmental impact of global copper demand on local communities in the Atacama mining hotspot as registered by tree rings - Nicolás C. Zanetta-Colombo; Tobias Scharnweber; Duncan A. Christie; Carlos A. Manzano; Mario Blersch; Eugenia M. Gayo; Ariel A. Muñoz; Zoë L. Fleming; Marcus Nüsser (Science of The Total Environment, 2024)

Between family variation in EPA and DHA storage among Atlantic salmon (Salmo salar) fed a fish oil-free diet - Zeyu Zhang; Frank Powell; Andrew K. Swanson; Elizabeth Boulding; Matthew L. Rise; Younes Miar; Marine Herlin; Stefanie M. Colombo (Aquaculture, 2024)

Assessment of meso- and microplastics distribution in coastal sediments and waters at the middle estuary of the Rio De La Plata, Argentina (SW Atlantic Ocean) - L. Santucci; M.D. Fernández-Severini; G.N. Rimondino; C.V. Colombo; G. Prieto; A.D. Forero-López; E.S. Carol (Science of The Total Environment, 2024)

High-Resolution In Situ Characterization of the Hydrochemical Variability Along the Fluvio-marine Transition of the Río de la Plata Estuary, Argentina - S. Heguilor; E. D. Speranza; L. M. Tatone; C. N. Skorupka; M. C. Migoya; J. C. Colombo (Estuaries and Coasts, 2024)

Microstructure of Deposited AISI M4 High Speed Steel On AISI D2 Tool Steel Substrate Using L-DED Process - Giovanna F. Colombo; Moysés L. de Lima; Mário Boccalini; Alzira V. O. Corrêa; Marcelo T. Veiga (BHM Berg- und Hüttenmännische Monatshefte, 2024)

Probiotic and synbiotic edible coatings: Effects on Lacticaseibacillus casei viability and general quality of minimally processed fruit during storage - Júlia Vitória Barbosa Dias; Whyara Karoline Almeida Costa; Dirceu de Sousa Melo; Kataryne Árabe Rimá de Oliveira; André Ulisses Dantas Batista; Evandro L. de Souza; Rosane Freitas Schwan; Tatiana Colombo Pimentel; Marciane Magnani (Food Bioscience, 2023)

OS04-02: Next Generation PBK modeling with PK-Sim for the prediction of chemical distribution in humans - R. Geci; D. Gadaleta; S. Proença; E. Colombo; M. García de Lomana; R. Ortega Vallbona; N. Kramer; A. Paini; L. Küpfer; S. Schaller (Toxicology Letters, 2023)

The impact of Li-bearing pegmatite mining on the dissolved geochemical signature of a mountain stream in the Pampean ranges, Central Argentina - Milagros Marqués; Andrea I. Pasquini; María Gabriela García; Verena A. Campodonico; Fernando Colombo; Diego M. Gaiero; Karina L. Lecomte (Sustainable Water Resources Management, 2023)

Psilocybin prevents reinstatement of alcohol seeking by disrupting the reconsolidation of alcohol-related memories - F. Benvenuti; D. Colombo; L. Soverchia; N. Cannella; E. Domi; R. Ciccocioppo (Psychopharmacology, 2023)

Study of the mechanical properties of thermoplastic polyurethane (TPU) recycled from end-of-life ski-boots and techno-economic analysis (TEA) of the mechanical recycling processes - A. Nanni; L. Crosetta; G. La Fauci; F. Biagi; M. Parisi; D. Colombo; M. Colonna (Sustainable Chemistry and Pharmacy, 2023)

Towards achieving circularity and sustainability in feeds for farmed blue foods - Stefanie M. Colombo; Koushik Roy; Jan Mraz; Alex H. L. Wan; Simon J. Davies; Sean M. Tibbetts; Margareth Øverland; David S. Francis; Melissa M. Rocker; Laura Gasco; Emma Spencer; Marc Metian; et al. (Reviews in Aquaculture, 2023)
The aims of this review are to describe the role of ‘blue‐food production’ (animals, plants and algae harvested from freshwater and marine environments) within a circular bioeconomy, discuss how such a framework can help the sustainability and resilience of aquaculture and to summarise key examples of novel nutrient sources that are emerging in the field of fed‐aquaculture species. Aquaculture now provides >50% of the global seafood supply, a share that is expected to increase to at least 60% within the next decade. Aquaculture is an important tool for reducing resource consumption in global protein production and increasing resilience to climate change and other global disruptions (i.e. pandemics, geo‐political instability). Importantly, blue foods also provide essential nutrition for a growing human population. Blue foods are helping to help the global goal of ‘zero hunger’ (United Nation's Sustainable Development Goal 2) while reducing the dependency on finite natural resources but further refinement and new solutions are needed to make the industry more ‘circular’ and sustainable, particularly with respect to sourcing raw materials for aquafeeds. This review describes the feed resources that are available or may be created within a circular bioeconomy framework, their role within the framework and in aquaculture and ultimately, how these resources contribute to de‐risking and establishing a resilient aquaculture production chain.

Invasive Aspergillosis in Patients with Acute Leukemia: Comparison Between Acute Myeloid and Acute Lymphoid Leukemia - Arnaldo L. Colombo; Maria Daniela Bergamasco; Simone A. Nouér; Paulo de Tarso Oliveira e Castro; Alessandro C. Pasqualotto; Flavio de Queiroz-Telles; Edson Abdala; Jessica F. Ramos; Diego R. Falci; Marcio Nucci (Mycopathologia, 2023)

Baseline assessment of microplastics in commercially important marine bivalves from New York, U.S.A. - Mackenzie L. Minder; Isabella G. Colombo; Konstantine J. Rountos (Marine Pollution Bulletin, 2023)

Correction to: The thyroid status reprograms T cell lymphoma growth and modulates immune cell frequencies - H. A. Sterle; M. L. Barreiro Arcos; E. Valli; M. A. Paulazo; S. P. Méndez Huergo; A. G. Blidner; F. Cayrol; M. C. Díaz Flaqué; A. J. Klecha; V. A. Medina; L. Colombo; G. A. Rabinovich; et al. (Journal of Molecular Medicine, 2023)

Sandstone petrofacies, deformational events and the dynamic of the Valle Fértil Lineament during the late Paleozoic (Paganzo Basin, northwestern Argentina) - Luis A. Spalletti; Carlos O. Limarino; Ferrán Colombo; Patricia L. Ciccioli; Carina E. Colombi (Journal of South American Earth Sciences, 2023)

Who let the young‐of‐the‐year ( YOY) up? The pelagic habitat as a nursery and feeding ground area for the YOY Argentine hake Merluccius hubbsi Marini, 1933 - Mauro Belleggia; Gustavo L. Alvarez‐Colombo; Betina A. Santos; Martin Castelletta; Belen Mattera (Journal of Fish Biology, 2022)
The young‐of‐the‐year (YOY) Argentina hake Merluccius hubbsi remained at particular distances off the seabed at pelagic habitat, in a nursery area located in the San Jorge Gulf off south‐western Atlantic. Older specimens were daylight distributed near the bottom in the demersal habitat. In this paper the authors show that the pelagic habitat is favourable for YOY hake compared to the surrounding demersal habitat by decreasing the probability of encounter with larger hake protecting the YOY against conspecific predation, and providing a better food supply. From 303 stomachs of pelagic YOY Argentine hake analysed (60–250 mm), 274 (90.43%) contained prey. Pelagic Argentine YOY hake fed almost exclusively on zooplanktonic crustaceans ( Euphausia spp. and Themisto gaudichaudii ). From 980 demersal specimens (14–82 cm), 572 (58.36%) contained prey, mainly the lobster krill Munida gregaria , followed by other hakes by cannibalism. The intensity of feeding was higher on pelagic layers. The allometric weight–length relationship revealed that the YOY Argentine hake find sufficient food in the pelagic habitat to live and develop, by increasing their relative body thickness. The cannibalism increases from close to zero when the YOY hake are c . 20 m off the seabed, to between 15% (cold season) and 20% (warm season) when they are 10 m off the seabed. These results suggest that the pelagic habitat is a feeding ground for YOY hake, and it is a favourable one compared to the surrounding demersal habitat by protecting the YOY from cannibalism. Pelagic YOY hakes were less abundant and more distant from the bottom during the cold season (14.3 m) than during warm one (11.4 m), probably because of natural mortality and progressive recruitment to demersal habits.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Nanopore Genome Sequencing and Variant Analysis of the Susceptible Candida auris Strain L1537/2020, Salvador, Brazil - Auke W. de Jong; Elaine C. Francisco; João Nóbrega de Almeida; Igor B. Brandão; Felicidade M. Pereira; Pedro H. Presta Dias; Magda M. de Miranda Costa; Regiane T. de Souza Jordão; Duong Vu; Arnaldo L. Colombo; Ferry Hagen (Mycopathologia, 2021)
Candida auris has been reported worldwide, but only in December 2020, the first strain from a COVID-19 patient in Brazil was isolated. Here, we describe the genome sequence of this susceptible C. auris strain and performed variant analysis of the genetic relatedness with strains from other geographic localities.

Molecular Identification and Antimicrobial Activity of Foliar Endophytic Fungi on the Brazilian Pepper Tree (Schinus terebinthifolius) Reveal New Species of Diaporthe - Germana D. dos Santos; Renata R. Gomes; Rosana Gonçalves; Gheniffer Fornari; Beatriz H. L. N. S. Maia; Claudia Schmidt-Dannert; Francois Gaascht; Chirlei Glienke; Gabriela X. Schneider; Israella R. Colombo; Juliana Degenhardt-Goldbach; João L. M. Pietsch; et al. (Current Microbiology, 2021)

Freshwater, Landlocked Grand Lake Strain of Atlantic Salmon (Salmo salar L.) as a Potential Genetic Source of Long Chain Polyunsaturated Fatty Acids Synthesis - Stefanie M. Colombo; Mohamed Emam; Brian C. Peterson; Jennifer R. Hall; Gary Burr; Zeyu Zhang; Matthew L. Rise (Frontiers in Marine Science, 2021)
Selection efforts focused on adaptation to plant-based diets, particularly the ability to synthesize polyunsaturated fatty acids (PUFA), are now emerging in aquaculture. Landlocked salmon (Grand Lake population; GL) may differ from the commercial Saint John River (SJR) strain in terms of PUFA metabolism. The objective of this study was to determine if GL salmon can contribute toward broodstock selection for enhanced PUFA synthesis. Two diets containing either fish oil (FO) or plant-based oil (FO-free) were fed to the SJR and GL strains (∼58 g/fish) for 16 weeks. Growth, liver, and muscle fatty acid (FA) content, and transcript expression of lipid metabolism and inflammation-related genes were evaluated. GL salmon fed the FO diet showed reduced growth compared to SJR salmon (fed either diet); however, GL salmon fed the FO-free diet, growth was not significantly different compared to any group. In liver, SJR salmon fed the FO-free diet had higher levels of n-6 PUFAs (21.9%) compared to GL fed the same diet (15.9%); while GL salmon fed the FO-free diet had higher levels of monounsaturated FAs (48.9%) compared with SJR salmon fed the same diet (35.7%). 20:5n-3 and 22:6n-3 were the same in GL and SJR salmon liver and muscle, respectively, fed the FO-free diet. In liver, GL salmon fed the FO-free diet had higher acac and acly compared to all treatments and had higher fasb compared to both strains fed the FO-diet. GL salmon fed the FO-free diet had higher cd36c and fabp3b in liver compared to GL salmon fed the FO diet and SJR salmon fed either diet. GL salmon fed the FO-free diet had higher lect2a and pgds in liver compared to SJR salmon fed the FO-free diet. In muscle, GL salmon fed the FO-free diet had higher fadsd5 and fadsd6b compared with both strains fed the FO diet. These results suggest there is a genetic basis behind the potential for GL salmon to utilize FO-free diets more efficiently than SJR salmon, with regards to FA metabolism.

The use of biomimetic tools for water quality monitoring: passive samplers versus sentinel organisms - M. Morrone; N. E. Cappelletti; L. M. Tatone; M. J. Astoviza; J. C. Colombo (Environmental Monitoring and Assessment, 2021)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Projected declines in global DHA availability for human consumption as a result of global warming - Stefanie M. Colombo; Timothy F. M. Rodgers; Miriam L. Diamond; Richard P. Bazinet; Michael T. Arts (Ambio, 2020)
Docosahexaenoic acid (DHA) is an essential, omega-3, long-chain polyunsaturated fatty acid that is a key component of cell membranes and plays a vital role in vertebrate brain function. The capacity to synthesize DHA is limited in mammals, despite its critical role in neurological development and health. For humans, DHA is most commonly obtained by eating fish. Global warming is predicted to reduce the de novo synthesis of DHA by algae, at the base of aquatic food chains, and which is expected to reduce DHA transferred to fish. We estimated the global quantity of DHA (total and per capita) currently available from commercial (wild caught and aquaculture) and recreational fisheries. The potential decrease in the amount of DHA available from fish for human consumption was modeled using the predicted effect of established global warming scenarios on algal DHA production and ensuing transfer to fish. We conclude that an increase in water temperature could result, depending on the climate scenario and location, in a ~ 10 to 58% loss of globally available DHA by 2100, potentially limiting the availability of this critical nutrient to humans. Inland waters show the greatest potential for climate-warming-induced decreases in DHA available for human consumption. The projected decrease in DHA availability as a result of global warming would disproportionately affect vulnerable populations (e.g., fetuses, infants), especially in inland Africa (due to low reported per capita DHA availability). We estimated, in the worst-case scenario, that DHA availability could decline to levels where 96% of the global population may not have access to sufficient DHA.

Elucidating the symbiotic interactions between a locally isolated microalga Chlorella vulgaris and its co-occurring bacterium Rhizobium sp. in synthetic municipal wastewater - L. Ferro; M. Colombo; E. Posadas; C. Funk; R. Muñoz (Journal of Applied Phycology, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Pumice clasts in cross stratified basalt-dominated sandstones and conglomerates. Characteristics and depositional significance: Huarenchenque Fm (Neuquén, Argentina) - F. Colombo; R. Bargalló; L. A. Spalletti; P. Enrique; I. Queralt (Journal of Iberian Geology, 2019)

In Situ Tissue Labeling of Cerebral Amyloid Using HIV-Related Tat Peptide - E. Maderna; L. Colombo; A. Cagnotto; G. Di Fede; A. Indaco; F. Tagliavini; M. Salmona; G. Giaccone (Molecular Neurobiology, 2018)

Beneficial and Safety Properties of a Corynebacterium vitaeruminis Strain Isolated from the Cow Rumen - M. Colombo; N. P. A. Castilho; S. D. Todorov; L. A. Nero (Probiotics and Antimicrobial Proteins, 2017)

Effects of aerobic exercise training on metabolism of nitric oxide and endothelin-1 in lung parenchyma of rats with pulmonary arterial hypertension - A. Zimmer; R. B. Teixeira; J. H. P. Bonetto; R. Siqueira; C. C. Carraro; L. M. Donatti; A. Hickmann; I. E. Litvin; A. E. G. Godoy; A. S. Araujo; R. Colombo; Adriane Belló-Klein (Molecular and Cellular Biochemistry, 2017)

Fatty acid alterations in the detritivorous Prochilodus lineatus promoted by opportunistic feeding on sewage discharges in the R ío de la P lata estuary - E. D. Speranza; M. Colombo; L. M. Tatone; N. Cappelletti; M. C. Migoya; J. C. Colombo (Journal of Fish Biology, 2016)
Muscle fatty acid profiles and PCB contents of the detritivorous species Prochilodus lineatus and its diet (stomach contents, settling particles and sediments) were analysed from reference and polluted areas of the Paraná‐Rio de la Plata basin, to evaluate the alterations produced by opportunistic feeding on sewage discharges. Overall muscle fatty acid composition was dominated by saturated and monounsaturated 16 and 18 carbon (18 C‐ FA ) components with reduced long‐chain polyunsaturated fatty acids ( LC‐PUFA ). Compared to sediments, settling particles and stomach contents were enriched in lipids and had a similar fatty acid composition. Opportunistic feeding on sewage detritus at Buenos Aires resulted in enhanced PCB and triglyceride accumulation, with higher proportions of 18 C‐ FA and lower proportions of 16:1 and LC‐PUFA compared to fish from northern pristine reaches of the basin. Mid‐Paraná showed intermediate values reflecting mixing of the North stock with migrating Buenos Aires P. lineatus identified by their lipid and contaminant profile. According to multivariate analyses, this geographical variation of fatty acid composition was strongly influenced by PCB concentration. Prochilodus lineatus assimilates the energy subsidy of sewage inputs through enhanced lipogenesis with dominant 18 C‐ FA and significant amounts of valuable LC‐PUFA . This lipid alteration facilitates the bioaccumulation of PCBs which in turn may reinforce the adipogenic effect of sewage feeding.

Paediatric nasopharyngeal cytology: a new diagnostic opportunity? - S. Torretta; P. Marchisio; M. R. Colombo; C. Rosazza; L. Pignataro (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

The thyroid status reprograms T cell lymphoma growth and modulates immune cell frequencies - H. A. Sterle; M. L. Barreiro Arcos; E. Valli; M. A. Paulazo; S. P. Méndez Huergo; A. G. Blidner; F. Cayrol; M. C. Díaz Flaqué; A. J. Klecha; V. A. Medina; L. Colombo; G. A. Rabinovich; et al. (Journal of Molecular Medicine, 2016)

Botanicals authentication in food, food supplements and herbal medicinal products - M. L. Colombo (Plant Biosystems, 2016)

Is the recent decrease in airborne Ambrosia pollen in the Milan area due to the accidental introduction of the ragweed leaf beetle Ophraella communa? - M. Bonini; B. Šikoparija; M. Prentović; G. Cislaghi; P. Colombo; C. Testoni; L. Grewling; S. T. E. Lommen; H. Müller-Schärer; M. Smith (Aerobiologia, 2015)

Sun‐induced fluorescence – a new probe of photosynthesis: First maps from the imaging spectrometer HyPlant - U. Rascher; L. Alonso; A. Burkart; C. Cilia; S. Cogliati; R. Colombo; A. Damm; M. Drusch; L. Guanter; J. Hanus; T. Hyvärinen; T. Julitta; et al. (Global Change Biology, 2015)
Variations in photosynthesis still cause substantial uncertainties in predicting photosynthetic CO 2 uptake rates and monitoring plant stress. Changes in actual photosynthesis that are not related to greenness of vegetation are difficult to measure by reflectance based optical remote sensing techniques. Several activities are underway to evaluate the sun‐induced fluorescence signal on the ground and on a coarse spatial scale using space‐borne imaging spectrometers. Intermediate‐scale observations using airborne‐based imaging spectroscopy, which are critical to bridge the existing gap between small‐scale field studies and global observations, are still insufficient. Here we present the first validated maps of sun‐induced fluorescence in that critical, intermediate spatial resolution, employing the novel airborne imaging spectrometer HyPlant . HyPlant has an unprecedented spectral resolution, which allows for the first time quantifying sun‐induced fluorescence fluxes in physical units according to the Fraunhofer Line Depth Principle that exploits solar and atmospheric absorption bands. Maps of sun‐induced fluorescence show a large spatial variability between different vegetation types, which complement classical remote sensing approaches. Different crop types largely differ in emitting fluorescence that additionally changes within the seasonal cycle and thus may be related to the seasonal activation and deactivation of the photosynthetic machinery. We argue that sun‐induced fluorescence emission is related to two processes: (i) the total absorbed radiation by photosynthetically active chlorophyll; and (ii) the functional status of actual photosynthesis and vegetation stress.

Flower and fruit structure of the endangered species Petagnaea gussonei (Sprengel) Rauschert (Saniculoideae, Apiaceae) and implications for its reproductive biology - O. De Castro; P. Colombo; L. Gianguzzi; R. Perrone (Plant Biosystems, 2015)

Bioaccumulation of dioxin-like PCBs and PBDEs by detritus-feeding fish in the Rio de la Plata estuary, Argentina - N. Cappelletti; E. Speranza; L. Tatone; M. Astoviza; M. C. Migoya; J. C. Colombo (Environmental Science and Pollution Research, 2015)

Direct numerical simulation of fully saturated flow in natural porous media at the pore scale: a comparison of three computational systems - M. Siena; J. D. Hyman; M. Riva; A. Guadagnini; C. L. Winter; P. K. Smolarkiewicz; P. Gouze; S. Sadhukhan; F. Inzoli; G. Guédon; E. Colombo (Computational Geosciences, 2015)

Combined effects of arbuscular mycorrhizal fungi and exogenous cytokinins on pomegranate (Punica granatum) under two contrasting water availability conditions - M. J. Bompadre; L. Fernández Bidondo; V. A. Silvani; R. P. Colombo; M. Pérgola; A. G. Pardo; A. M. Godeas (Symbiosis, 2015)

Performance of Bemisia tabaci (Genn.) Biotype B (Hemiptera: Aleyrodidae) on Weeds - L D M Sottoriva; A L Lourenção; C A Colombo (Neotropical Entomology, 2014)

AtAPOSTART1, an Arabidopsis thaliana PH-START domain protein involved in seed germination - F. Resentini; S. Vanzulli; G. Marconi; L. Colombo; E. Albertini; S. Masiero (Plant Biosystems, 2014)

Behavior of Dioxin Like PCBs and PBDEs During Early Diagenesis of Organic Matter in Settling Material and Bottom Sediments from the Sewage Impacted Buenos Aires’ Coastal Area, Argentina - N. Cappelletti; C. N. Skorupka; M. C. Migoya; L. Tatone; M. Astoviza; J. C. Colombo (Bulletin of Environmental Contamination and Toxicology, 2014)

B25716/1: a novel albumin-binding Gd-AAZTA MRI contrast agent with improved properties in tumor imaging - E. Gianolio; C. Cabella; S. Colombo Serra; G. Valbusa; F. Arena; A. Maiocchi; L. Miragoli; F. Tedoldi; F. Uggeri; M. Visigalli; P. Bardini; S. Aime (JBIC Journal of Biological Inorganic Chemistry, 2014)

Trends in Surface Water Chemistry in Acidified Areas in Europe and North America from 1990 to 2008 - Øyvind A. Garmo; Brit Lisa Skjelkvåle; Heleen A. de Wit; Luca Colombo; Chris Curtis; Jens Fölster; Andreas Hoffmann; Jakub Hruška; Tore Høgåsen; Dean S. Jeffries; W. Bill Keller; Pavel Krám; et al. (Water, Air, & Soil Pollution, 2014)

Apple ( Malus domestica L. Borkh) as an emerging model for fruit development - G. Eccher; S. Ferrero; F. Populin; L. Colombo; A. Botton (Plant Biosystems, 2014)

Protein interactions guiding carpel and fruit development in Arabidopsis - H. Herrera-Ubaldo; E. Zanchetti; L. Colombo; S. de Folter (Plant Biosystems, 2014)

Effects of Nicotine on Cardiovascular Remodeling in a Mouse Model of Systemic Hypertension - E. Sage Colombo; Joshua Davis; Mehran Makvandi; Mario Aragon; Selita N. Lucas; Michael L. Paffett; Matthew J. Campen (Cardiovascular Toxicology, 2013)

Differential efficiency of two strains of the arbuscular mycorrhizal fungus Rhizophagus irregularis on olive (Olea europaea) plants under two water regimes - M. J. Bompadre; M. C. Rios De Molina; R. P. Colombo; L. Fernandez Bidondo; V. A. Silvani; A. G. Pardo; J. A. Ocampo; A. M. Godeas (Symbiosis, 2013)

Molecular Identification of Melanised Non-Sporulating Moulds: A Useful Tool for Studying the Epidemiology of Phaeohyphomycosis - Daniel W. C. L. Santos; Ana Carolina B. Padovan; Analy S. A. Melo; Sarah S. Gonçalves; Viviane R. Azevedo; Marilia M. Ogawa; Tainá Veras Sandes Freitas; Arnaldo L. Colombo (Mycopathologia, 2013)

Trace Metals in Settling Particles from the Sewage Impacted Buenos Aires Coastal Area in the Río de la Plata Estuary, Argentina - L. M. Tatone; C. Bilos; C. N. Skorupka; J. C. Colombo (Bulletin of Environmental Contamination and Toxicology, 2013)

Migratory behaviour of a dominant detritivorous fish Prochilodus lineatus evaluated by multivariate biochemical and pollutant data - E. D. Speranza; N. Cappelletti; M. C. Migoya; L. M. Tatone; J. C. Colombo (Journal of Fish Biology, 2012)
This paper studies the migration pathways and ranges of a dominant detritivorous fish Prochilodus lineatus along pollution gradients in the Río de la Plata basin using multivariate analysis of biochemical and pollutant data. Biochemical composition (water, ash, lipids, proteins, carbohydrates, neutral lipids classes and fatty acids), aliphatic hydrocarbons (ALI), polychlorinated biphenyls (PCB), linear alkylbenzenes (LAB) and organochlorine pesticides (OClP) were determined in muscle samples of P. lineatus collected in Metropolitan Buenos Aires, the lower Paraná River (Paraná: 200–1000 km from Buenos Aires) and the middle Paraná and Paraguay Rivers (North: 1000–1400 km north). Biochemical variables and pollutants exhibited large variability [Lipids 1·1–89·5% wet mass; ALI 1·4–413; LABs not detectable (n.d.)–115·2; PCBs n.d.–27·9; OClPs n.d.–11·8 µg g −1 dry mass], due to the contrast of Buenos Aires with North fish. Fish from Buenos Aires were fatty (lipids 24·7 ± 12·3% wet mass), enriched in 18 carbon fatty acids and severely contaminated (ALI 152·4 ± 72·3; LABs 65·1 ± 26·4; PCBs 15·2 ± 6·8; OClPs 1·8 ± 1·9 µg g −1 dry mass mean ± s.d .). In contrast, fish from North were lean (4·1 ± 3·1% wet mass), enriched in long chain (>20 carbons) polyunsaturated fatty acids, with average one to two orders of magnitude lower pollutant levels (ALI 41·2 ± 51·9; PCBs 2·2 ± 3·5; LABs 8·8 ± 21·1; OClPs 0·67 ± 0·75 µg g −1 dry mass mean ± s.d .). Paraná showed intermediate values in all variables, denoting the mixing of different fish stocks. Based on principal component analysis, 14 outliers from 60 North and Paraná samples (representing 26 from 108 individual fish) were identified as pertaining to the Buenos Aires group with very similar lipid and pollutant levels. Data suggest that P. lineatus migrates a highly variable distance, exceeding 800–1000 km in multiple spatial and temporal overlapping ranges. Chemometric analysis of biochemical and pollutant data effectively discriminates fish according to the chemical signature acquired by detritus feeding in pristine and contaminated urban or industrial areas.

Bisphenol A endocrine disruptor complete degradation using TiO2 photocatalysis with ozone - Alessandra Colombo; Giuseppe Cappelletti; Silvia Ardizzone; Iolanda Biraghi; Claudia L. Bianchi; Daniela Meroni; Carlo Pirola; Francesca Spadavecchia (Environmental Chemistry Letters, 2012)

Heme oxygenase 1 (HO-1) challenges the angiogenic switch in prostate cancer - M. Ferrando; G. Gueron; B. Elguero; J. Giudice; A. Salles; F. Coluccio Leskow; E. A. Jares-Erijman; L. Colombo; R. Meiss; N. Navone; A. De Siervi; E. Vazquez (Angiogenesis, 2011)

Immunostimulatory and cytotoxic activities of Indigofera suffruticosa (Fabaceae) - Flávia C.M. Lopes; Tamara R. Calvo; Lucas L. Colombo; Wagner Vilegas; Iracilda Z. Carlos (Natural Product Research, 2011)

With time on our side? Task-dependent compensatory processes in graceful aging - M. Berlingeri; G. Bottini; L. Danelli; F. Ferri; D. Traficante; L. Sacheli; N. Colombo; M. Sberna; R. Sterzi; G. Scialfa; E. Paulesu (Experimental Brain Research, 2010)

Remote sensing of larch phenological cycle and analysis of relationships with climate in the Alpine region - L. BUSETTO; R. COLOMBO; M. MIGLIAVACCA; E. CREMONESE; M. MERONI; M. GALVAGNO; M. ROSSINI; C. SINISCALCO; U. MORRA DI CELLA; E. PARI (Global Change Biology, 2010)
This research aims at developing a remote sensing technique for monitoring the interannual variability of the European larch phenological cycle in the Alpine region of Aosta Valley (Northern Italy) and to evaluate its relationships with climatic factors. Phenological field observations were conducted in eight test sites from 2005 to 2007 to determine the dates of completion of different phenological phases. MODerate Resolution Imaging Spectrometer (MODIS) 250 m 16‐days normalized difference vegetation index (NDVI) time series were fitted with double logistic curves and the dates corresponding to different features of the curves were determined. Comparison with field data showed that the features of the fitted NDVI curve that allowed the best estimate of the start and end of the growing season were the zeroes of its third derivative (MAE of 6 and 4 days, respectively). The start and end of season were also estimated with the spring warming (SW) and growing season index (GSI) phenological models. MODIS start and end of season dates generally agreed with those obtained by the SW and GSI climate‐driven phenological models. However, phenological models provided erroneous results when applied in years with anomalous meteorological conditions. The relationships between interannual variability of the larch phenological cycle and climate were investigated by comparing the mean start and end of season yearly anomalies with air temperature anomalies. A strong linear relationship ( R 2 =0.91) was found between mean spring temperatures and mean start of season dates, with an increase of 1 °C in mean spring temperature leading to a 7‐day anticipation of mean larch bud‐burst date. Leaf coloring dates were found to be best related with mean September temperature ( R 2 =0.77), but with higher spring temperatures appearing to lead to earlier leaf coloring.

Effect of Early Introduction of Microencapsulated Diet to Larval Atlantic Halibut, Hippoglossus hippoglossus L. Assessed by Microarray Analysis - H. M. Murray; S. P. Lall; R. Rajaselvam; L. A. Boutilier; R. M. Flight; B. Blanchard; S. Colombo; V. Mohindra; M. Yúfera; S. E. Douglas (Marine Biotechnology, 2010)

Vertical Fluxes and Accumulation of Trace Metals in Superficial Sediments of the Río de la Plata Estuary, Argentina - L. M. Tatone; C. Bilos; C. N. Skorupka; J. C. Colombo (Bulletin of Environmental Contamination and Toxicology, 2009)

Detection of Helicobacter pylori, Enterococcus faecalis, and Pseudomonas aeruginosa in the subgingival biofilm of HIV-infected subjects undergoing HAART with chronic periodontitis - L. Souza Gonçalves; R. Souto; A. P. V. Colombo (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

Morphological analysis of female gametophyte development in the bel1 stk shp1 shp2 mutant - R. Battaglia; V. Brambilla; L. Colombo (Plant Biosystems, 2008)

Update on the Genus Trichosporon - Thomas C. Chagas-Neto; Guilherme M. Chaves; Arnaldo L. Colombo (Mycopathologia, 2008)

European larch phenology in the Alps: can we grasp the role of ecological factors by combining field observations and inverse modelling? - M. Migliavacca; E. Cremonese; R. Colombo; L. Busetto; M. Galvagno; L. Ganis; M. Meroni; E. Pari; M. Rossini; C. Siniscalco; U. Morra di Cella (International Journal of Biometeorology, 2008)

Cost-effectiveness of pneumococcal vaccination for prevention of invasive pneumococcal disease in the elderly: an update for 10 Western European countries - S. M. A. A. Evers; A. J. H. A. Ament; G. L. Colombo; H. B. Konradsen; R. R. Reinert; D. Sauerland; K. Wittrup-Jensen; C. Loiseau; D. S. Fedson (European Journal of Clinical Microbiology & Infectious Diseases, 2007)

Systematic GIS-based landslide inventory as the first step for effective landslide-hazard management - A. Colombo; L. Lanteri; M. Ramasco; C. Troisi (Landslides, 2005)

EU-OSTID: A Collection of Transposon Insertional Mutants for Functional Genomics in Rice - L. J. G van Enckevort; Gaëtan Droc; Pietro Piffanelli; Raffaella Greco; Cyril Gagneur; Christele Weber; Víctor M. González; Pere Cabot; Fabio Fornara; Stefano Berri; Berta Miro; Ping Lan; et al. (Plant Molecular Biology, 2005)

A Preliminary Trial Using Multi-target Polymerase Chain Reaction (multiplex PCR) and Restriction Fragment Length Polymorphism (PCR-RFLP) on the Same Feedstuffs to Detect Tissues of Animal Origin - F. Colombo; E. Marchisio; I.E. Trezzi; V. Peri; L. Pinotti; A. Baldi; G. Soncini (Veterinary Research Communications, 2004)

Transpositional behaviour of an Ac/Ds system for reverse genetics in rice - R. Greco; P. B. F. Ouwerkerk; R. J. de Kam; C. Sallaud; C. Favalli; L. Colombo; E. Guiderdoni; A. H. Meijer; J. H. C. Hoge†; A. Pereira (Theoretical and Applied Genetics, 2003)

Successful Treatment of an Aspergillus Brain Abscess with Caspofungin: Case Report of a Diabetic Patient Intolerant of Amphotericin B - A. L. Colombo; R. C. Rosas (European Journal of Clinical Microbiology & Infectious Diseases, 2003)

Global Distribution and Outcomes for Candida Species Causing Invasive Candidiasis: Results from an International Randomized Double-Blind Study of Caspofungin Versus Amphotericin B for the Treatment of Invasive Candidiasis - A. L. Colombo; J. Perfect; M. DiNubile; K. Bartizal; M. Motyl; P. Hicks; R. Lupinacci; C. Sable; N. Kartsonis (European Journal of Clinical Microbiology & Infectious Diseases, 2003)

Identification of Moulds Belonging to the Penicillium Genus using a Polymerase Chain Reaction (PCR-SSCP) Method Followed by 'Computer Assisted' Statistical Analysis of the Electrophoretic Patterns - F. Colombo; L. Vallone; R. Capoferri; I. Dragoni (Veterinary Research Communications, 2003)

Ovule-specific MADS-box proteins have conserved protein-protein interactions in monocot and dicot plants - R. Favaro; R. Immink; V. Ferioli; B. Bernasconi; M. Byzova; G. Angenent; M. Kater; L. Colombo (Molecular Genetics and Genomics, 2002)

Genomic changes in transgenic rice (Oryza sativa L.) plants produced by infecting calli with Agrobacterium tumefaciens - M. Labra; C. Savini; M. Bracale; N. Pelucchi; L. Colombo; M. Bardini; F. Sala (Plant Cell Reports, 2001)

Sequence comparison and phylogenetic analysis of fish nodaviruses based on the coat protein gene - L. Dalla Valle; E. Negrisolo; P. Patarnello; L. Zanella; C. Maltese; G. Bovo; L. Colombo (Archives of Virology, 2001)

Effect of drying methods on retention of moist sucralfate gel properties - L. Maggi; P. L. Catellani; E. Fisicaro; P. Santi; F. Zani; G. Massimo; P. Colombo (AAPS PharmSciTech, 2000)

Development of a sensitive diagnostic assay for fish nervous necrosis virus based on RT‐PCR plus nested PCR - L Dalla Valle; L Zanella; P Patarnello; L Paolucci; P Belvedere; L Colombo (Journal of Fish Diseases, 2000)
A polymerase chain reaction (PCR)‐based assay to detect nervous necrosis virus (NNV) in fish was developed by using two sets of primers designed on a highly conserved region of the coat protein gene encoded by RNA2 of NNV. The first pair of primers amplified a fragment of 605 bp by one‐step reverse‐transcription (RT)‐PCR, while the second pair amplified an internal segment of 255 bp by nested PCR. Addition of nested PCR increased the assay sensitivity 100‐fold when carried out in a separate tube (two‐step assay) and 10‐fold when performed in the same tube (one‐step assay). The sensitivity of the two‐step assay was 104 times higher than that of virus cultivation. Nested PCR served also to confirm the specificity of the first amplification, as verified also by Southern hybridization analysis and direct sequencing. In species known to be susceptible to infection, such as European sea bass, Dicentrarchus labrax , and gilthead seabream, Sparus aurata , NNV was often detectable in brain tissue by RT‐PCR alone but only by the two‐step assay in blood, sperm, ovarian tissue or larvae. The same was true for sperm and ovarian tissue of shi drum, Umbrina cirrosa . NNV was also detected in the brains of Japanese red seabream, Pagrus major and brown meagre, Sciaena umbra , suggesting that these species can also be infected. No NNV was detected in samples of Artemia salina nauplii and rotifers obtained from a fish farm with an NNV outbreak. The inclusion of nested PCR in the assay appears to be necessary to screen out NNV‐positive broodfish by blood sampling and testing of their larval progeny.

Immunolocalization of the petunia floral binding proteins 7 and 11 during seed development in wild-type and expression mutants ofPetunia hybrida - P. E. Wittich; R. F. de Heer; X. -F. Cheng; H. Kieft; L. Colombo; G. C. Angenent; A. A. M. van Lammeren (Protoplasma, 1999)

Fungemia in cancer patients in Brazil: Predominance of non-albicans species - Marcio Nucci; Maria Isabel Silveira; Nelson Spector; Fernanda Silveira; Eduardo Velasco; Carlos Alberto Martins; Andrea Derossi; Arnaldo L. Colombo; Wolmar Pulcheri (Mycopathologia, 1998)

Acute Toxicity of Organophosphorus Insecticides to Marine Invertebrates - L. Guzzella; A. Gronda; L. Colombo (Bulletin of Environmental Contamination and Toxicology, 1997)